Effects of Individual and Institutional Factors for Sustainable Chains and Production - Korhan Arun; Saniye Yıldırım Özmutlu (Verimlilik Dergisi)
Purpose: This study aims to examine the impacts of institutional pressures and individual adaptation performance on the adoption of green supply chain practices and reverse logistics, and their effects on production-based CO2 emissions, focusing on emerging markets with a detailed case study of Türkiye.Methodology: The research methodology employed structural equation modeling (SEM) and SmartPLS for the analysis of the data. This approach allowed for an in-depth examination of the relationships between institutional pressures, individual adaptive performance, green supply chain practices, reverse logistics, and CO2 emissions.Findings: The findings reveal a nuanced relationship where institutional pressures directly impact reverse logistics but show minimal direct influence on green supply chain practices or CO2 emissions reduction. In contrast, individual adaptive performance is crucial in enhancing both green supply chain practices and reverse logistics. Notably, reverse logistics is significantly effective in reducing CO2 emissions. Originality: This study enriches the literature by revealing how institutional pressures and individual adaptive performance influence green supply chain management in emerging markets, particularly demonstrating through the case of Türkiye that the impact of within-field variability on the adoption of superior practices depends on individual adaptive performance.